REAP: A two minute cell fractionation method - Suzuki, Keiko; Bose, Pinaki; Leong-Quong, Rebecca YY; Fujita, Donald J; Riabowol, Karl (BMC research notes, 2010)
The translocation or shuttling of proteins between the nucleus and cytoplasm (nucleocytoplasmic transport [NCPT]) is often a rapid event following stimulation with growth factors or in response to stress or other experimental manipulations. Commonly used methods to separate nuclei from cytoplasm employ lengthy steps such as density gradient centrifugation which exposes cells to non-physiological hyperosmotic conditions for extended time periods resulting in varying degrees of leakage between the nucleus and cytoplasm. To help maintain and quantify nuclear:cytoplasmic ratios of proteins, agents such as leptomycin B have been employed to be able to better analyze NCPT by inhibiting nuclear export. To track NCPT in the absence of these experimental manipulations that could introduce unknown artefacts, we have developed a rapid method that appears to produce pure nuclear and cytoplasmic fractions, suitable for obtaining accurate estimates of the nuclear:cytoplasmic ratios of proteins known to undergo NCPT. We have developed a Rapid, Efficient And Practical (REAP) method for subcellular fractionation of primary and transformed human cells in culture. The REAP method is a two minute non-ionic detergent-based purification technique requiring only a table top centrifuge, micro-pipette and micro-centrifuge tubes. This inexpensive method has proven to efficiently separate nuclear from cytoplasmic proteins as estimated by no detectible cross-contamination of the nucleoporin and lamin A nuclear markers or the pyruvate kinase and tubulin cytoplasmic markers. REAP fractions also mirrored TNFα induced NF-κB NCPT observed in parallel by indirect immunofluorescence. This method drastically reduces the time needed for subcellular fractionation, eliminates detectable protein degradation and maintains protein interactions. The simplicity, brevity and efficiency of this procedure allows for tracking ephemeral changes in subcellular relocalization of proteins while maintaining protein integrity and protein complex interactions.